The Impact of Science Experiment Methods in Improving Early Childhood Cognitive Skills - Triana Widyastuti; Fauzi Fauzi (Gagasan Pendidikan Indonesia, 2024)
There are six aspects of early childhood development. One of those aspects that need to get stimulus at an early age is cognitive development. In the learning process, the science experiment is one of the learning methods that can be applied. It is an interesting method for children because they can do an experiment and explore a lot of things. This study aims to find out the used of science experiment methods in early childhood learning activity and the impact of the science experiment methods to their cognitive development. The method of this research is literature review. The author collects the other resources from the others journal with the same topics. The results showed that there was an effect of science experiments in improving the cognitive abilities of early childhood. The results can be a recommendation to teachers or anyone to applied science experiment in order to improve early childhood cognitive ability.